Pengaruh Pajak Tangguhan Dan Kepemilikan Manajerial Terhadap Persistensi Laba Dengan Tingkat Utang Sebagai Variabel Pemoderasi - I Gede Adi Indrawan; Dhea Amelia; Lodang Prananta Widya Sasana (Bisnis-Net, 2023)
ABSTRACTThe Effect of Deferred Tax and Managerial Ownership on Profit Persistence with DebtLevels as a Moderating Variable (Empirical Study of Property and Real Estate CompaniesListed on the IDX for the 2017-2021 period). This study aims to analyze the Effect ofDeferred Tax and Managerial Ownership on Profit Persistence with Debt Levels asModerating Variables in property and real estate sector companies listed on the IndonesiaStock Exchange (IDX) for the 2017-2021 period. This research is a type of quantitativeresearch and uses assosiative methods. The sampling technique used is purposive samplingmethod. The data analysis technique used was panel data regression analysis, with dataprocessing using the Eviews version 10 program. The results showed that simultaneouslyDeffered Tax and Managerial Ownership had an effect on Earning Persistence. PartiallyDeffered Tax has no effect on Earning Persistence, Managerial Ownership has no effecton Earning Persistence. Debt Level is not able to moderate the effect of Deffered Tax onEarning Persistence, and Debt Level is not able to moderate the effect of ManagerialOwnership on Earning Persistence.Keywords: Deffered Tax, Managerial Ownership, Debt Level, Earning Persistence